Côte d'Ivoire's electricity challenge in 2050: Reconciling economic development and climate commitments. (January 2022) - Assoumou, Edi; McIsaac, Florent
Abstract: In closing its economic gap with emerging markets, Côte d'Ivoire will face a substantial increase in electricity demand over the next three decades. Côte d'Ivoire has signed the Paris Agreement that aims to achieve a balance between anthropogenic emissions by sources, including electricity, and absorption by sinks of greenhouse gases in the second half of the century. This This paper develops a forward-looking tool to explore electricity technology investment paths compatible with both rapidly increasing electricity demand and the Paris Agreement. We build a TIMES model for Côte d'Ivoire and run scenarios with two sets of reasonable assumptions that represent two competing, and probable visions of the future costs of coal and photovoltaic technologies. The results show that a carbon tax of about US21 in 2035 and US82 in 2050 on electricity generation will ensure low-carbon electricity generation in line with the Paris Agreement. Although a low-carbon energy mix would create significantly more jobs, the two main challenges in achieving this energy mix will be to install as much as 24 GW of photovoltaic power by 2050 or to achieve a socially accepted carbon tax. Highlights: We develop a TIMES model of the electricity sector for Côte d'Ivoire that provides least-cost solutions for power systems. Our estimates show that electricity demand could increase by a factor of 4.5 by 2050. Least cost solutions show that solar PV could provide at least 18% of total electricity generation in 2050. A carbon price of US21 in 2035 to US82 in 2050 ensures that the electricity mix will be compatible with climate goals. In the case of a low-cost solar scenario, PV capacity is up to 24 GW and storage is nearly 15 GW between 2030 and 2050.